2020
DOI: 10.1002/csc2.20198
|View full text |Cite
|
Sign up to set email alerts
|

Identification of variant α‐kafirin alleles associated with protein digestibility in grain sorghum

Abstract: Owing to its unique adaptation to challenging environments, sorghum [Sorghum bicolor (L.) Moench] remains a vital food security crop for millions of smallholder communities in sub‐Saharan Africa. Elsewhere, the crop is used as an important feed ingredient. One key constraint undermining food and feed value of sorghum is reduced protein digestibility, which has been attributed to numerous causes. The aim of the present study was to investigate the impact of DNA sequence variations in genes coding for sorghum se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…One nutritional constraint to the use of sorghum as food is the poor digestibility of sorghum proteins in cooking (Tesso et al, 2008 ). Duressa et al ( 2020 ) have reported sorghum accessions with a protein content as high as 15% but with different digestibility percentages (a measure of the susceptibility of protein to proteolysis). For example, the sorghum accession SC663 with a protein content of 15.5% had a high protein digestibility of 70.77%.…”
Section: Discussionmentioning
confidence: 99%
“…One nutritional constraint to the use of sorghum as food is the poor digestibility of sorghum proteins in cooking (Tesso et al, 2008 ). Duressa et al ( 2020 ) have reported sorghum accessions with a protein content as high as 15% but with different digestibility percentages (a measure of the susceptibility of protein to proteolysis). For example, the sorghum accession SC663 with a protein content of 15.5% had a high protein digestibility of 70.77%.…”
Section: Discussionmentioning
confidence: 99%
“…To solve the problem of poor digestibility of kafirins various genetic and biotechnological approaches may be used: experimental induction of mutants with impaired synthesis or altered amino acid composition of kafirins [15]; identification of naturally occurring allelic variants of kafirins [16][17][18][19]; obtaining transgenic plants with the genetic constructs that induce silencing of γ-and/or α-kafirin genes [20][21][22][23]; editing the nucleotide sequences of kafirin genes in order to obtain lines with complete or partial knockout of these genes [24].…”
Section: Introductionmentioning
confidence: 99%
“…1k ). In the second experiment, dropout a segment of the Kaf ( γ-Kafirin, Sobic.002G211700 ) gene 30 was tested using two sgRNAs ( Sb-Kaf-CR1 and -CR3 ) (Supplementary Fig. 4 ) in Tx430.…”
Section: Resultsmentioning
confidence: 99%